The CsCl- and CsN03-induced high temperature oxidation of Nimonic-90 alloy at 1123 K - Mohammed Misbahul, Amin (Elsevier Science B.V., 2009)
Link to publisher's homepage at http://www.elsevier.com/wps/find/homepage.cws_home